Integrating digital and in-person therapy for PTSD: feasibility and acceptability of blended trauma-focused cognitive therapy in routine care - Lundin, Johan; Jansson-Fröjmark, Markus; Gustafsson-Björverud, Linda; Grey, Nick; Santoft, Fredrik; Ehlers, Anke; Carlbring, Per; Lundgren, Tobias; Bragesjö, Maria; Salomonsson, Sigrid (Frontiers in Psychiatry, 2024)
Introduction: Access to evidence-based psychological therapy for posttraumatic stress disorder (PTSD) is limited. Blended Trauma-focused Cognitive Therapy (bTF-CT), merging internet-modules with a few therapy sessions, may be a pathway to enhance treatment access while maintaining the benefits of face-to-face therapy.Objectives: This study aimed to evaluate the feasibility, acceptability, and preliminary effectiveness of bTF-CT for PTSD in routine care, as well as the feasibility of assessments and data collection. Method: A single-arm design was adopted. bTF-CT was provided to 17 participants across two psychiatric and one primary care clinic. Assessments were conducted pre, during, post and 6months following treatment. We assessed feasibility and acceptability via self-report questionnaires, retention, and attrition rates. Preliminary treatment effectiveness was estimated using the PTSD Symptom Checklist (PCL-5) was used to assess PTSD symptom severity. Results: Treatment satisfaction was high with a mean score of 28.7 out of 32 on the Client Satisfaction Questionnaire (SD = 3.5). The dropout rate was low, with 88% treatment retention. Program adherence was satisfactory, with scores ranging from 2.13 to 3.13 out of 4 on the internet intervention patient adherence scale. On the PCL-5, 88% made a reliable change, 64% demonstrated a clinically significant change, and the mean change from pre to post was 24 points (d = 2.13). Some negative effects were reported, such as unpleasant memories, feelings, and disrupted sleep, but these were temporary according to symptom scales. Conclusions: bTF-CT appears to be acceptable, feasible, and potentially effective when delivered in routine care. A large-scale non-inferiority trial to assess effectiveness compared to a gold-standard treatment is warranted. The study was registered at Clinicaltrials.gov (NCT04881643) Highlights:• Blended trauma-focused cognitive therapy (bTF-CT) for PTSD, a fusion of internetdelivered and in-person therapy, was found to be acceptable, feasible and potentially effective for patients with PTSD in routine primary and secondary care. • bTF-CT yielded high treatment satisfaction and low drop-out rates.• Large reductions in symptoms of PTSD and depression were obtained, with effects maintained at a six-month follow-up.